PENGARUH KUALITAS PELAYANAN, HARGA, PROMOSI, DAN CITRA MEREK TERHADAP KEPUASAN PELANGGAN MELALUI KEPUTUSAN PEMBELIAN - Aris Budiono (Equilibrium: Jurnal Penelitian Pendidikan dan Ekonomi, 2020)
This study aims to find the effect of service, price, promotion, and brand image on customer satisfaction through purchasing decisions. The study population is customers of PT Indomarco, located in the southern Tangerang region. Proportional sampling technique is simple random sampling. A sample of 137 agents. Primary data were collected through a questionnaire using a Likert scale model that has been tested for validity and reliability. Data analysis technique used is Path Analysis (Path Analysis). The results of the study are: simultaneously the effect of Service Quality, Price, Promotion, and Brand Image on Purchasing Decisions is 15.6%, the effect of Service Quality, Price, Promotion, Brand Image, and Purchasing Decisions on Customer Satisfaction simultaneously is 22.9%, Service Variable (0.011), and Brand Image (0.021) which have a positive effect on purchasing decisions, Service Variable (0.004) and Promotion (0.015) which have a positive effect on customer satisfaction, Promotion Variables can affect satisfaction variables indirectly through intervening variables namely decisions purchase at PT Indomarco sub Tangerang Selatan.Keyword :  Keywords: Service quality, price, promotion, brand image, purchasing decisions, customer satisfaction